Service Portfolio Management Plan at PPTI Stikom Surabaya Using Standard ITIL Version 3 - Handoko, Januaryoputra Setyo; Tanuwijaya, Haryanto; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Pengembangan dan Penerapan Teknologi Informasi (PPTI) is a part in the Institut Bisnis dan Informatika Stikom Surabaya (Surabaya Stikom) whose role is important to ensure the course of Systems and Information Technology (STI) to support the business processes running on Stikom Surabaya. Currently PPTI not yet have a standard for managing IT services to determine whether the service is worth it or not to use, it is because PPTI not have IT service portfolio. Given these constraints PPTI can not know whether the service is functioning properly or not as an attempt to evaluate the IT services. The solution in the above problems, the planning service portfolio management based on standard ITIL version 3. Purpose to produce a document IT service portfolio that generates the details of IT services and IT service management in PPTI Stikom Surabaya. The results of the planning service portfolio management in the form of document service portfolio, which contains 10 services Retired services, 5 Service Service Catalogue, and 8 services Service Pipeline, as well as the standard document review services portfolio, investment analysis values and priorities, as well as IT service management and document review procedures service portfolio, investment analysis values and priorities, as well as IT service management.